NETs Lead to Sympathetic Hyperactivity After Traumatic Brain Injury Through the LL37-Hippo/MST1 Pathway - Zhu, Kaixin; Zhu, Yibai; Hou, Xiaoxiang; Chen, Wen; Qu, Xiaolin; Zhang, Yelei; Li, Zhenxing; Wang, Chunhui; Chen, Jigang; Lv, Liquan; Wang, Junyu; Zhang, Danfeng; et al. (Frontiers in Neuroscience, 2021)
Background: Paroxysmal sympathetic hyperactivity (PSH) is one of the important reasons for the high mortality and morbidity of traumatic brain injury (TBI). We aim to explore the role of the neutrophil extracellular traps (NETs) in the pathogenesis of sympathetic hyperexcitability after TBI and the underlying mechanisms, providing evidence for clinical treatment. Methods: Enzyme-linked immunosorbent assay was used to assess the plasma metanephrine and normetanephrine levels which represented the variation of the sympathetic system after TBI with rat diffuse axonal injury (DAI) model. NETs in the paraventricular nucleus (PVN) and circulating blood were examined using immunofluorescence and flow cytometry. Neutrophils-microglia co-culture system was established to further explore the effect of NETs on PSH and its mechanisms. Results: After TBI, metanephrine and normetanephrine levels began to increase at 9 hours and peaked at 72 hours. After the injury, the level of NETs kept increasing at 24 hours and 72 hours in the PVN. A positive correlation was found between the concentration of the PVN NETs and blood catecholamine. Flow cytometry of peripheral blood cells revealed that NETs level in the injury group was higher than that in the control group. Immunofluorescence results confirmed the presence of NETs in the PVN after TBI. The positive result of immunoprecipitation suggested a correlation effect between LL37 and P2X7. Peptidyl arginine deiminase-4 (PAD4) inhibitor could inhibit the expression levels of MST1, YAP, and IL-1β. The hippo/MST1 pathway inhibitor could inhibit the expression levels of YAP and IL-1β. Conclusions: NETs formation in the PVN might be associated with sympathetic hyperactivity after TBI, which might relate to the activation of microglia cells and increased secretion of IL-1β via the hippo/MST1 pathway.